Synthesis, Characterisation and Catalytic Evaluation of Castor Oil-Templated Mesoporous Sulfated Solid Acid Catalysts for Esterification Reaction - Nyandoro, Stephen S.; Elimbinzi, Elianaso (Tanzania Journal of Engineering and Technology, 2023)
In bio-refinery and other catalytic reactions, heterogeneous catalysts confer advantage over homogenous catalysts due to minimized recovery and separation costs. However, templating surfactant and solid support for the synthesis of heterogeneous catalysts ought to consider their cheap sources and environmentally friendliness for their sustainable use. Thus, with the vision to make the process significantly benign, in the present work, solid acids were synthesised from renewable sources (castor oil as surfactant and rice husk as the source of silica). The synthesised castor oil-templated mesoporous sulfonic acid modified catalysts (SO3H-MTS and SO3H-MT-RHS) were characterised and evaluated for catalytic esterification of acetic acid (C2), hexanoic acid (C6), lauric acid (C12), palmitic acid (C16), and ricinoleic acid (C18) with butanol at 110 °C. Physicochemical properties of the synthesised materials were characterised by nitrogen porosimetry, X-ray powder diffraction, thermogravimetry, X-ray Photoelectron Spectroscopy (XPS), and Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS). The porosimetric analysis of the synthesised materials revealed a type IV adsorption-desorption isotherm reminiscent of the mesoporous structures. The surface area of the synthesised materials decreased upon functionalisation by sulfonic group. The DRIFTS and XPS confirmed the attachment of sulfonic functional group on the synthesised materials. Evaluation of the catalytic performance of the synthesized materials was determined through analysis of carboxylic acid conversions using gas chromatographic technique. SO3H-MTS gave higher acid conversions compared to SO3H-MT-RHS. The sulfated solid acid catalysts showed good catalytic activity on the esterification with conversion ranging from 96-37% for C2-C18 with butanol at 110 °C within 6 h. Such castor oil-templated mesoporous sulphated solid acid catalysts can therefore be applied in biodiesel production upon process optimisation. Keywords: Castor oil-templated mesoporous; sol-gel; solid acid catalysts; esterification; rice husk-derived silica; C2-C18.